The effect of zinc chloride on the passive avoidance memory of female rats ovariectomized in the pre-pubertal stage - Pooran Ghahramani; Hooman Eshagh Harooni; Seyed Raza Fatemi Tabatabaei; Ahmad Ali Moazedi (Fiyz̤, 2019)
Background: Many studies have shown that zinc has an important effect on learning, memory and cognition. On the other hand, ovariectomy in adult female rats reduces memory and learning. Also, regarding the contradictory reports on the effects of zinc chloride on memory and learning, this study aimed to examine the effect of zinc chloride on passive avoidance memory of ovariectomized female rats in the pre-pubertal stage. Materials and Methods: In this experiment, fifty female rats were ovariectomized at postnatal day 21-22 and were divided into six groups; control, sham (saline), ovariectomized (saline) and the ovariectomized groups received zinc chloride 5, 10 and 20 mg/kg at puberty. Then on postnatal day 77, passive avoidance memory was examined by the shuttle box. Different doses of zinc chloride were administered 30 min before training and the test took place 24 hours later. Results: Ovariectomy decreased the stopping time in the dark room compared with the sham group, non-significantly. Groups received zinc chloride 5 mg/kg showed a significant increase in stopping time in the dark room compared to the ovariectomized group received saline (P<0.01). Conclusion: The findings of this study show that pre-pubertal ovariectomy has no effect on passive avoidance memory and injection of zinc chloride can be reduced memory and learning.